Organizational Communication Management at PT. Paramount Enterprise International in Efforts to Increase Product Sales - Alfin Ortavian; Ahmad Toni (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
Communication has grown widely and has entered all aspects as well as levels ranging from interpersonal communication to organizational communication. Communication management carried out by the leadership of PT. Paramount Enterprise International is basically an important point in today's market competition. It is known that during the Covid-19 Pandemic the sales level of PT. Paramount Enterprise International demonstrates stability. This shows that communication is going well between the implementing human resources both between leaders and subordinates, related divisions, and between staff. All parties in the company can understand the message from the company's leaders well, so that the company's goals expected by the company's leaders can be achieved. This type of research is descriptive with a qualitative approach, with data collection methods used namely through interviews and direct observation. Data collection techniques are carried out through data reduction, data presentation and drawing conclusions.The results of this study indicate that organizational communication management is very effective in providing appropriate information to all levels within the company. So that the purpose of PT. Paramount Enterprise International to increase sales can be understood by all members of the company, from the leader down to the grassroots. Organizational communication is carried out very directed and centered on one direction, namely the company leader. Through communication networks and organizational communication channels, it helps the overall dissemination of information.